Elevated high sensitivity cardiac troponin T among men with HIV who use stimulants: A cross-sectional study of subclinical cardiovascular injury - Michaela E. Larson; Yue Pan; Lisa Reidy; Emily M. Cherenack; Sabina Hirshfield; Keith J. Horvath; Elise D. Riley; Savita Pahwa; Suresh Pallikkuth; Claudia Martinez; Adam W. Carrico (PLoS ONE, 2026)
People with HIV (PWH) experience elevated cardiovascular disease risk compared to people without HIV. Stimulant use may further increase subclinical myocardial injury among PWH, but data on cardiovascular biomarkers, including serum high-sensitivity cardiac troponin T (hs-cTnT) in this population is limited. This cross-sectional secondary analysis included 72 cisgender men with and without HIV enrolled in a South Florida cohort. Stimulant exposure was defined as any non-prescribed stimulant use in the past 3 months and/or a reactive urine toxicology screen, creating four HIV-by-stimulant use groups (i.e., HIV+Stim + , HIV+Stim-, HIV-Stim + , and HIV-Stim-). hs-cTnT was measured using a Roche high-sensitivity assay, with values below the limit of detection treated as undetectable. We used a two-part model (logistic for detectability; log-normal among participants with detectable hs-cTnT), adjusted for age and recent tobacco use, with sensitivity analyses adding renal function and cardiometabolic factors. After adjusting for age and recent tobacco use, HIV+Stim+ participants had higher odds of detectable hs-cTnT (aOR = 7.48, 95% CI: 1.25, 44.62) and higher estimated mean concentration of hs-cTnT (β = 0.51, p = 0.031, mean = 12) than the HIV-Stim- group. Exploratory analyses suggested a positive dose-response association between amphetamine metabolite levels and hs-cTnT ( r (11) = 0.86, p < 0.0001). Co-occurring HIV and stimulant use were associated with higher hs-cTnT in this sample. However, given that hs-cTnT may reflect a range of acute, subacute, and chronic processes, and the small sample size and restricted generalizability, these findings should be interpreted as exploratory and hypothesis-generating and require confirmation in larger studies.